Incidencia de la obtención del rebote en relación al lugar de lanzamiento del balón en los partidos de baloncesto de la liga nacional infantil efectuado en la Provincia de los Ríos 2016 - Cubero Moran, Jorge Michael (2016)
Today in the world of basketball one of the most spectacular moments of the game is when the ball going to the hoop, not in and out rebounded, causing a fight of players leaping grab of it, this is one of the technical elements more important the game is to get the ball by the offensive or defensive, after a launch failed, in Ecuador most won or lost by the teams that participated in Little league 2016 matches should be to obtaining the defensive or offensive rebound in the development of games played this being one of the fundamental elements to take control of the game. This study was aimed to determine the incidence having obtaining rebound in relation to the location of the release of the ball in the basketball games of child domestic league incurred in the Province of Los Rios, through field research in the same all the matches played were observed, the relationship between the missed shot and managed to rebound by an observation guide was established and results were validated using the test chip squared to determine whether it is proportional to the missed shot and rebound achieved depending on the launch site within the results could be seen: the amount and type of rebound that was obtained by computer during the juvenile child championship was 9846 releases the highest incidence were obtained by the defense and a lower percentage offense, when releases are made from long distance the higher incidence of obtaining the rebound is the center of the court, being the place of the left lower incidence area